Dynamics of cell cycle proteins involved in Toxoplasma gondii-induced bovine NET formation - Velásquez, Zahady D.; Peixoto, Raquel; Gärtner, Ulrich; Hermosilla, Carlos; Taubert, Anja; Conejeros, Iván (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) formation is one important host innate defense mechanism elicited by polymorphonuclear neutrophils (PMN). NETs are composed by chromatin and proteins with microbicidal and signaling activity. So far, there is one report on Toxoplasma gondii-triggered NETs for cattle, however, exact mechanisms, including signalling pathways and dynamics governing this reaction remains largely unknown. Recently, involvement of cell cycle proteins was demonstrated for phorbol myristate acetate (PMA)-triggered human PMN-derived NETs. Here we studied the involvement of cell cycle proteins in T. gondii-induced NETs in exposed bovine PMN. Through confocal and transmission electron microscopy we discovered that Ki-67 and lamin B1 signals are upregulated and re-located during T. gondii-induced NETosis. Nuclear membrane disruption was also observed as a hallmark of NET formation in bovine PMN confronted with viable T. gondii tachyzoites, mimicking some steps of mitosis. However, we did not observe centrosome duplication as previously described for human PMN-derived NET formation stimulated with PMA.